Mythological, Historical and Personal: the Story of Creation of Mary Renault’s Dilogy “Theseus” - M. V. Artamonova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the mythological, historical and personal aspects of the creation of the Theseus dilogy (“The King Must Die”, 1958; “The Bull from the Sea”, 1962) by the English author Mary Renault (1905-1983). The relevance of the study is due to the need to comprehend these mythocentric works, which are the result of the synthesis of various types of artistic mythologism. The study is based on the principles of comparative historical, biographical and historical-genetic methods of analysis of a work of art. The traditions of mythologism in the English literature of the twentieth century are analyzed. The following features are distinguished: the mythological tradition of the twentieth century reflects the pressing issues of our time; modern mythologism implies a change or destruction of the canon. It is stated that the principle of historicity of M. Renault novels is implemented on the basis of archaeological and anthropological works of her contemporaries. It is proved that two types of artistic mythologism are simultaneously used in dilogy: demythologization and remythologization. The authors argue that this approach makes mythogenesis possible within the framework of a realistic narrative. In addition, the question about the implementation of the author’s creative intention to attract public attention to the problems of same-sex relationships is raised.